Endothelial cell-derived microRNAs-containing extracellular vesicles and diabetic retinopathy in a mouse model of diabetes - Meili Wu; Haoyuan Zhou; Tianyi Zong; Ziwen Li; Yujuan Cao; Qian Yang; Tong Mu; Tianhua Xie; Xiaolu Wang; Yong Yao (In Vitro Cellular & Developmental Biology - Animal, 2026)
Diabetic retinopathy (DR) is a leading cause of visual impairment and blindness in industrialized countries, resulting from diabetes mellitus. Prostaglandin E 2 (PGE 2 ), synthesized by cyclooxygenases, contributes to inflammation and apoptosis via the E-prostanoid receptor 2 (EP 2 R). Our previous studies demonstrated that EP 2 R antagonists mitigate inflammation and microvascular dysfunction in streptozotocin (STZ)-induced DR. Given the paracrine role of extracellular vesicles (EVs) in DR, we hypothesized that EVs derived from human endothelial cells (ECs) may regulate the PGE 2 /EP 2 R pathway in DR. Using an STZ-induced diabetic mouse model, we administered intravitreal injections of AAV2-shEP 2 R and evaluated retinal histology, optical coherence tomography, and biochemical markers. EV morphology, size, and concentration from high glucose (HG)-treated ECs were analyzed. Small RNA expression in plasma EVs from DR patients was assessed via deep sequencing. EP 2 R inhibition via AAV2-mediated knockdown significantly reduced retinal vascular leakage, leukostasis, and retinal Müller cell (rMC) activation. MiRNA profiling revealed elevated levels of miR-423-5p and miR-21-5p in EVs from HG-treated ECs, which were suppressed in EVs from EP 2 R antagonist-treated cells. Notably, deep sequencing of plasma EVs from DR patients confirmed significant upregulation of these miRNAs compared to healthy controls. MiR-423-5p and miR-21-5p function as key paracrine mediators promoting Müller cell activation and retinal microvascular dysfunction in DR. These findings highlight the potential of circulating EVs as vehicles for miRNA-based therapeutic interventions in DR.